ANALYTICAL REVIEW OF WORK LIFE BALACNCE IN THE PRESENCE OF THE TECHNOLOGICAL INNOVATIONS. - Rahat Ali, Syed (IJRDO - Journal of Social Science and Humanities Research, 2017)
The purpose of this research was to discover and examine on the relationship between WORK LIFE BALANCE IN THE PRESENCE OF THE TECHNOLOGICAL INNOVATIONS. Focus was on how increased work hours of the new economy may interfere with familial relations in the future. Background information and various theories on work-life conflict are discussed. Problem statement, consequences, and solutions are referenced to provide more insight on how to establish a balance between work and family spheres. Implications of work-life balance and conflict in the presence of Technological innovation were analyzed for future consequences are also elaborated.